2007
DOI: 10.1080/15574090802095823
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Early Drinking Contexts of Women “Coming Out” as Lesbian and Current Alcohol Use

Abstract: Several decades of research show that lesbians are at risk for hazardous drinking. Compared with heterosexual women, lesbians are less likely to abstain from drinking, less likely to decrease their alcohol consumption as they age, and more likely to report alcohol-related problems. Stress associated with lesbian identity and reliance on lesbian or gay bars for socialization and support are frequently posited--but largely untested--explanations for lesbians' heightened risk. Results from general population stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 58 publications
3
28
1
Order By: Relevance
“…Further, lesbian, bisexual and queer women who come out before age 21 report earlier onset of drinking than those who come out later, perhaps as a consequence of being exposed to heavy drinking communities at an earlier age (Parks and Heller 2013). earlier coming out may also be associated with earlier experiences of homophobia, which also increases drinking (Parks, Hughes, and Kinnison 2007). Some studies have identified problems related to bars being popular meeting places, such as lesbian, bisexual and queer women feeling a social pressure to drink, or consuming alcohol to cope with feelings of self-consciousness in these settings, particularly during the 'coming out' phase (condit et al 2011).…”
Section: Alcohol Socialisation and Normalisationmentioning
confidence: 88%
“…Further, lesbian, bisexual and queer women who come out before age 21 report earlier onset of drinking than those who come out later, perhaps as a consequence of being exposed to heavy drinking communities at an earlier age (Parks and Heller 2013). earlier coming out may also be associated with earlier experiences of homophobia, which also increases drinking (Parks, Hughes, and Kinnison 2007). Some studies have identified problems related to bars being popular meeting places, such as lesbian, bisexual and queer women feeling a social pressure to drink, or consuming alcohol to cope with feelings of self-consciousness in these settings, particularly during the 'coming out' phase (condit et al 2011).…”
Section: Alcohol Socialisation and Normalisationmentioning
confidence: 88%
“…Many of the findings of this study are consistent with other research related to alcohol consumption and alcohol-related problems among sexual minority women. For example, other studies have linked sexual minority women’s alcohol consumption with both individual and environmental influences such as abuse and alcoholism in the family of origin (Hughes, et al, 2007; Parks 1999b) and the influence of patronizing bars and participating in other alcohol-oriented drinking contexts in the process of coming out and creating community (Heffernan, 1998; Hequembourg & Brallier, 2009; Parks & Hughes, 2004, 2005, 2007; Parks, et al, 2007). The degree to which family members were supportive or judgmental about the respondents’ sexual identity was consistently identified as having had a significant impact, both in adolescence and adulthood; this finding is consistent with literature suggesting that parental support has an important impact on health outcomes for sexual minority women and men (Needham & Austin, 2010; Ryan, Huebner, Diaz, & Sanches, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies that explore lesbian experiences with alcohol, the role of alcohol in creating community and developing identity, and meanings associated with use of alcohol and social contexts that are alcohol-centered are particularly useful in examining the complex factors that contribute to disparities in risk for alcohol problems among sexual minority women (Parks, 1999b; Parks & Hughes, 2004, 2005, 2007; Parks, Hughes, & Kinnison, 2007). Several qualitative studies have noted the prevalence of the lesbian bar as a meeting place for sexual minority women (Gruskin, et al, 2006; Hequembourg & Brallier, 2009; Parks, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…These findings, and those of other studies (e.g., Herek, Norton, Allen, & Sims, 2010), suggest that sexual minority youth are coming out at ages earlier than their older counterparts. Given evidence that younger age of coming out is associated with hazardous drinking as well as elevated health risks of childhood maltreatment, gay-related harassment, and suicidality (Corliss, Cochran, Mays, Greenland, & Seeman, 2009; Friedman, Marshal, Stall, Cheong, & Wright, 2008; Parks, Hughes, & Kinnison, 2007), contemporary sexual minority youth may be at even greater risk of hazardous drinking than their older sexual minority counterparts.…”
Section: Early Risk Factors For Hazardous Drinkingmentioning
confidence: 99%